Compilation of Social Media and Social Networking Sites Features - Ruzainisuhanaliza, Abdul Muni; Ruzaini, Abdullah Arshah; Tuty Asmawaty, Abdul Kadir; Mazlina, Abdul Majid; Rozlina, Mohamed (2013)
There are various social media that are currently available for users and their main objective is to let users keep in touch with friends worldwide or meeting new people. This paper tries to provide an insight on classification of existing social media and social networking sites main features. Then, we highlight that all social media and social networking features can be merged as one to construct a single social networking site to be accessed in a dashboard page view. We also perform a comparison study to illustrate that almost all social media have the features of social networking sites. From the classification and comparative study, we found that there are numerous social network sites designed with different combinations features. Thus, this research intends to determine most recent features needed in a social networking site.